The Effect of Academic Self-efficacy on CBT and SOCA Exam Achievement of Neuropsychiatry Block - A. Aisyah Febriani; Suliati P. Amir; Zulfahmidah; Marliyanti Nur Rahmah; Farah Ekawati Mulyadi (Universitas Baiturrahmah, 2026)
Introduction: Academic self-efficacy, defined as an individual's belief in their ability to overcome academic challenges, has consistently been linked to improved academic performance. However, its impact on key assessments in medical education, such as the Computer-Based Test (CBT) and the Student Oral Case Analysis (SOCA), remains underexplored. This study examines the influence of academic self-efficacy on knowledge achievement in the CBT and SOCA exams among medical students in the Neuropsychiatry block at the Faculty of Medicine, Muslim University of Indonesia. Objective: This study aims to assess the impact of academic self-efficacy on students’ knowledge achievement in both the CBT and SOCA exams and to provide insight into the role of self-efficacy across different exam formats. Methods: This cross-sectional observational study involved 376 students from the 2022 cohort. Academic self-efficacy was measured using a validated questionnaire, and test scores were analyzed using descriptive statistics. The relationship between self-efficacy and test scores was evaluated using Pearson’s correlation test. Results: The study found a significant positive correlation between academic self-efficacy and SOCA exam scores (r = 0.183, p = 0.000), although the correlation was weak. No significant relationship was found between self-efficacy and CBT scores (r = -0.075, p = 0.148). The majority of students reported high self-efficacy, with the average SOCA score (83.78) significantly higher than the CBT score (60.08). Conclusion: Academic self-efficacy significantly influences performance in interactive, communication-based exams like SOCA but has minimal impact on multiple-choice exams like CBT, which rely on recall or recognition. These findings emphasize the importance of fostering self-efficacy in medical education. Educational institutions should consider interventions such as self-efficacy training, learning strategies, and critical thinking development to enhance students' confidence and academic success.